Snakes and ladders : mind games in Genesis 2 and 3 - Gous, I. G. P. (Journal for semitics, 2010)
Biblical scholars often live in a kind of in-between world, where they are seen as either too scientific for the faith community, or not scientific enough for the world of science. They gain wonderful insights, but have no-one to share them with. Genesis 2-3 is a point in case. Church doctrine expects this text to be historically true, while modern minds see it as a pre-scientific, historically impossible story. The interpretations by biblical scholars help understand the flow of thought and the use of motifs which are not necessarily understood by current readers of the text. However, questions regarding the truth and meaning of the passage still remain. In an attempt to escape from the impasse, insights on the architecture of belief by a clinical psychologist, Jordan Peterson, are used to demarcate domains of understanding in the world. The world as a place of things is explored by using the formal methods of natural science, while the world of action is the world of value, and is explored by using techniques of narrative. Seen in this manner, ancient myths, such as those found in Genesis 2-3, need not be taken as outdated portrayals of ideas which can be discarded, but as dated yet still valid, even universal truths, to be found in human minds then and now, and still enabling us to cope with real life issues.